Occurrence of ergot in seed lots of grasses harvested in different regions of Poland - Wiewióra , Barbara; Prończuk, Maria (Plant Breeding and Seed Science, 2006)
The ergot (Claviceps purpurea) incidence in seed samples of Poa pratensis, Lolium perenne, L. multiflorum, Festuca rubra and F. pratensis cultivars originating from different regions of grass cultivation in Poland was detected in 1999 – 2002. Each year, about hundred twenty cultivars of different species were tested. It was found that number of seed replaced by sclerotia significantly varied and depended on the year of seed harvest, species and cultivar tested and region of grass grown for seed. The highest level of Claviceps purpurea sclerotia almost for all grass species was detected in 1999. The highest number of seed replaced by sclerotia was found in sowing material of Poa pratensis for all years of testing. Ergot in seed lots of L. multiflorum and F. pratensis were detected at trace levels. Differences in susceptibility to Claviceps purpurea among cultivars were observed. However, significant variation in occurrence of ergot sclerotia were noted for the same cultivar harvested in different region of Poland. It was found that size of sclerotia depended on the host - grass species and the year of seed harvest. Significant differences were noted particularly in the length and weight of sclerotia.